The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
Proceedings of the 2020 CHI Conference on Human Factors in Computing Systems 2020
DOI: 10.1145/3313831.3376187
|View full text |Cite
|
Sign up to set email alerts
|

Experiential Qualities of Whispering with Voice Assistants

Abstract: We present a Research through Design project that explores how whispering influences the ways people experience and interact with voice assistants. The research project includes a co-speculation workshop and the use of a design probe, which culminated in the production of a design fiction short film. Our design-led inquiry contributes with experiential qualities of whispering with voice assistants: creepiness, trust, and intimacy. Furthermore, we present how whispering opens up new dimensions of how and when v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(10 citation statements)
references
References 43 publications
(43 reference statements)
1
9
0
Order By: Relevance
“…Other opportunities can be imagined when using the voice-body continuums vHAI framework as a starting point. Non-human animal voices and biological voices, as well as musical voices; whispering to but also the whispers of a vocal agent [142]. We can again turn to popular culture for inspiration.…”
Section: Explorations Within and Beyond The Voice-body Continuumsmentioning
confidence: 99%
“…Other opportunities can be imagined when using the voice-body continuums vHAI framework as a starting point. Non-human animal voices and biological voices, as well as musical voices; whispering to but also the whispers of a vocal agent [142]. We can again turn to popular culture for inspiration.…”
Section: Explorations Within and Beyond The Voice-body Continuumsmentioning
confidence: 99%
“…Rogers et al [35] use props in flms to speculate on the nature of internet health of VAs. In a similar approach, Parviainen and Søndergaard [34] use short flms to expose trust in terms of our willingness to share and show vulnerabilities with machines. Seymour and Van Kleek [36] ask us to question our trust of VAs by using design fction to exaggerate our relationship with non-human machines, but that behave as if they are, in order to establish that VAs are clearly "not our friends".…”
Section: Speculation and Immaterials Voicesmentioning
confidence: 99%
“…Earlier research has noted how interacting with technologies that could be assigned agency was also a source of creepiness. Studies describing interactions with voice assistants [59,69] and with autonomous cars [14,49,50] found that both were perceived as creepy. These examples show that creepiness can be experienced where artefacts take an assumed social presence and possibly violate norms related to this presence.…”
Section: Creepy Technologiesmentioning
confidence: 99%